Letter (copy) : Shipment for Spain - Citrine, Walter, 1887-1983
030-0053-001 International WMC/AC/17 17th September, 1938. Mr. W. Schevenels, International Federation of Trade Unions, 9, avenue d'Orsay, PARIS VIIe. Dear Comrade Schevenels, SHIPMENT FOP SPAIN. Further to our telephone conversation on 15th instant, we have now been informed by the Scottish Trades Union Congress that they are ordering their goods for Spain through the Scottish Co-operative Wholesale Society, and that they require exact details as to how each case of goods is to be marked for shipment to Valencia. We also learn that the boat is leaving Glasgow on September 25th and perhaps you will be good enough to convey this information to our Spanish comrades. We shall be communicating with you again in the next day or so, giving you particulars of the consignment. Meanwhile, our Scottish friends are asking to receive the marking instructions by Tuesday morning, first post. Will you, therefore, kindly telephone this information to us on Monday? Yours sincerely, General Secretary. 292/946/30/53